2019
DOI: 10.3389/fonc.2019.00211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-Derived Growth Factor and DDX5 Promote Carcinogenesis and Progression of Endometrial Cancer by Activating β-Catenin

Abstract: Background: Our previous work determined the correlation between high nuclear expression of hepatoma-derived growth factor (HDGF) and clinicopathological data of endometrial cancer (EC); however, the modulatory mechanisms and biological role of HDGF in EC have not been reported. Methods: Lentiviral particles carrying human HDGF short hairpin RNA (shHDGF-1, -2, and -3) vector and plasmids for HDGF, DDX5, and β-catenin expression were, respectively introduced into EC cells to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…HDGF was originally obtained from the conditioned media of HuH-7 hepatoma cells [ 19 ]. It has been widely reported as an oncogenic factor promoting tumor pathogenesis including nonsmall cell lung carcinoma (NSCLC), endometrial cancer, nasopharyngeal carcinoma, breast cancer, and liver cancer in previous studies [ 20 – 25 ]. In a recent study, Wang et al found that methyltransferase-like 3 (METTL3) mediated m(6)A modification of HDGF mRNA and increased its mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…HDGF was originally obtained from the conditioned media of HuH-7 hepatoma cells [ 19 ]. It has been widely reported as an oncogenic factor promoting tumor pathogenesis including nonsmall cell lung carcinoma (NSCLC), endometrial cancer, nasopharyngeal carcinoma, breast cancer, and liver cancer in previous studies [ 20 – 25 ]. In a recent study, Wang et al found that methyltransferase-like 3 (METTL3) mediated m(6)A modification of HDGF mRNA and increased its mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…T24 and 253J cells were digested with trypsin (Gibco, USA) and dissociated repeatedly to prepare a single cell suspension. Migration assays were performed as described previously 20. After rubbing away the cells failed to through the membrane and washing with PBS three times, these chambers were photographed using an upright fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the involvement of HDGF in the regulation of the WNT/β-catenin pathway. [32][33][34] Accordingly, we tested whether miR-939 affects WNT/βcatenin signaling in PCa. To this end, we conducted Western blotting to quantify the important molecules associated with the WNT/β-catenin pathway in DU145 and PC3 cells transfected with agomir-939 in the presence of either pc-HDGF or pcDNA3.1.…”
Section: Mir-939 Overexpression Deactivates the Wnt/β-catenin Pathwaymentioning
confidence: 99%